Structure Insights Into Photosystem I Octamer From Cyanobacteria - Chen, Ming; He, Yujie; Liu, Dongyang; Tian, Lijin; Xu, Pengqi; Liu, Xuan; Pan, Yihang; Dong, Shuqi; He, Jun; Zhang, Ying (Frontiers in Microbiology, 2022)
Diversity of photosystem oligomers is essential to understand how photosynthetic organisms adopted to light conditions. Given by the structural and physiological significance, the assemblies of PSI supercomplex is of great interest in both chloroplast and cyanobacteria recently. In this study, two novel photosystem I supercomplexes were isolated for the first time from the low light incubated culture of filamentous cyanobacterium Anabaena sp. PCC 7120. These complexes were defined as PSI hexamers and octamers through biochemical and biophysical characterization. Their 77K emission spectra indicated that the red forms of chlorophylls seemed not to be affected during oligomerization. By cryo-EM single particle analysis, a near-atomic (7.0 Å) resolution structure of PSI octamer was resolved, and the molecular assemblies of stable PSI octamer was revealed.